CSF and Serum Levels of Inflammatory Markers in PD: Sparse Correlation, Sex Differences and Association With Neurodegenerative Biomarkers - Lerche, Stefanie; Zimmermann, Milan; Wurster, Isabel; Roeben, Benjamin; Fries, Franca Laura; Deuschle, Christian; Waniek, Katharina; Lachmann, Ingolf; Gasser, Thomas; Jakobi, Meike; Joos, Thomas O.; Schneiderhan-Marra, Nicole; et al. (Frontiers in Neurology, 2022)
Background An involvement of the central-nervous and peripheral, innate and adaptive immune system in the pathogenesis of Parkinson's disease (PD) is nowadays well established. Objectives We face several open questions in preparation of clinical trials aiming at disease-modification by targeting the immune system: Do peripheral (blood) inflammatory profiles reflect central (CSF) inflammatory processes? Are blood/CSF inflammatory markers associated with CSF levels of neurodegenerative/PD-specific biomarkers? Methods Using a multiplex assay we assessed 41 inflammatory markers in CSF/serum pairs in 453 sporadic PD patients. We analyzed CSF/serum correlation as well as associations of inflammatory markers with clinical outcome measures (UPDRS-III, H&Y, MoCA) and with CSF levels of α-synuclein, Aβ1−42, t-Tau, p181-Tau and NFL. All analyses were stratified by sex as the immune system shows relevant sex-specific differences. Results Correlations between CSF and serum were sparse and detected in only 25% (9 out of 36) of the analysable inflammatory markers in male PD patients and in only 38% (12 out of 32) of female PD patients. The most important pro-inflammatory mediators associated with motor and cognitive decline as well as with neurodegenerative/PD-specific biomarkers were FABP, ICAM-1, IL-8, MCP-1, MIP-1-beta, and SCF. Results were more robust for CSF than for serum. Interpretation Levels of central-nervous and peripheral inflammatory markers might be regulated independently of each other with CSF inflammatory markers reflecting CNS pathology more accurately than peripheral markers. These findings along with sex-specific characteristics have to be considered when designing clinical trials aiming at disease-modification by targeting the immune system.